Literary theory and the claims of history : postmodernism, objectivity, multicultural politics - Mohanty, Satya P. (Satya Prakash), 1954- (Cornell University Press, 1997)
Drawing on detailed analyses of reference, interpretation, and the nature value, Satya P. Mohanty defends a "postpositivist realist" conception of objectivity as a legitimate ideal of all inquiry. He outlines a realist theory of social identity and multicultural politics, showing why radical moral universalism and cultural diversity need to be seen a complementary, rather than competing ideals.
Keywords: Criticism -- History -- 20th century.; Literature, Modern -- 20th century -- History and criticism -- Theory, etc.; Postmodernism (Literature); Multiculturalism.; Critique -- Histoire -- 20e siècle.; Littérature -- 20e siècle -- Histoire et critique -- Théorie, etc.; Postmodernisme (Littérature); Multiculturalisme.; multiculturalism.; Criticism; Multiculturalism; Geschichtsbewusstsein; Literaturtheorie; Literatuurtheorie.; Postmodernisme.; Culturele verschillen.; Objectiviteit.; 1900-1999; Criticism, interpretation, etc.; History; Electronic books.